The Scientific Reliability of International Corruption Rankings - Németh, Erzsébet; Vargha, Bálint Tamás; Pályi, Katalin Ágnes (Public Finance Quarterly, 2019)
Owing to its hiding nature, corruption is difficult to measure. However, measurements lacking sufficient methodological grounds and the rankings so created pose just as much of economic risk as the corruption itself. The objective of the present study is to examine the methodological compliance of the calculation of the most well-known corruption perceptions index after having reviewed the specific literature and by using the method of document analysis. The most important criticisms formed against corruption measures in the international specific literature also highlight that in the most cases the independence of the organizations issuing the corruption measures, the transparency of data sources used and the applied methodology are not ensured. It follows from all of the above, and due to improper compilation of the respondent group and the inadequacies of the summary of the data sources - in the absence of methodological substantiation - the results are not suitable for comparing the countries, to draw scientific conclusions, and they do not even make a diagnosis related to the phenomenon examined which could serves as an efficient tool for making the appropriate policy decisions.